High barrier packaging film, preparation method and application in thermal runaway-proof jet insulation board packaging for power lithium battery

By modifying the zirconium-containing cage-containing silsesquioxane to the surface of the expanded vermiculite, a composite high-temperature barrier composition is prepared for the preparation of a high-barrier packaging film, which solves the problem of insufficient heat sealing strength in the sealing area of ​​the vacuum insulation plate, and realizes the It has the effect of high sealing strength and wide heat sealing temperature range, and is suitable for thermally-free and out-of-control spraying insulation board of power lithium batteries.

CN118893884BActive Publication Date: 2025-01-03SUZHOU ZIJIN PLASTIC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411371089.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

The vacuum insulation plate fails due to air leakage during use, mainly due to insufficient heat sealing strength caused by poor sealing area, which leads to an increased risk of thermal runaway jet accidents.

Method used

The surface covalent modification method is used to modify the zirconium-containing cage-containing silsesquioxane to the hydroxylated expanded vermiculite surface to prepare a composite high-temperature-resistant barrier composition, and a high-barrier packaging film is prepared through a coextrusion blow molding process, including external protection. The structural layer, the intermediate barrier structural layer and the internal heat sealing structural layer improve the sealing strength and heat sealing temperature range.

Benefits of technology

It significantly reduces the permeability of water vapor and oxygen, improves the sealing strength, widens the heat sealing temperature range, and reduces thermal conductivity, improves the barrier performance and heat sealing performance of the packaging film. It is suitable for thermal runaway injection of power lithium batteries. Insulating plate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118893884B_ABST
    Figure CN118893884B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of research and development of insulation board packaging films, and discloses a high-barrier packaging film, a preparation method and an application in the packaging of thermal runaway-proof jet insulation boards for power lithium batteries. The invention comprises: preparing a zirconium-containing cage-type silsesquioxane containing a hydrolyzable functional group, modifying the zirconium-containing cage-type silsesquioxane to the surface of hydroxylated expanded vermiculite by a surface covalent modification method, and preparing a composite high-temperature-resistant barrier composition; arranging the product structure of the packaging film to include an external protective structure layer, an intermediate barrier structure layer and an internal heat-sealing structure layer, adding the composite high-temperature-resistant barrier composition to the external protective structure layer and the intermediate barrier structure layer of the packaging film, and adopting a co-extrusion blow molding film-forming process to prepare a high-barrier packaging film, wherein the film has the technical advantages of high barrier performance, low thermal conductivity, high sealing strength and a wide sealing temperature range, and can be used for packaging thermal runaway-proof jet insulation boards for power lithium batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of research and development of thermal insulation board packaging films, and specifically to a high-barrier packaging film, a preparation method and an application in the packaging of thermal insulation boards for preventing thermal runaway of power lithium batteries. Background Art

[0002] Power lithium batteries are widely used in various electric vehicles due to their high power density and high charging efficiency. However, the energy storage part and energy conversion part of lithium batteries exist in the same space, which can easily cause chain exothermic reactions in the case of overcharging, puncture, and collision, resulting in thermal runaway accidents such as smoke, fire, and even explosion. In recent years, the problem of thermal runaway propagation in battery packs has been mainly solved through thermal protection technology. Thermal protection technology adds an insulation layer (mainly a vacuum insulation panel) in the battery pack to block the spread of thermal runaway from the runaway cell to the surrounding cells, reducing the damage to the battery pack and the incidental destructive effects.

[0003] Vacuum insulation panels have extremely low thermal conductivity and are gaining more and more attention in the field of thermal protection. Vacuum insulation panels are composed of core materials, getters and barrier films. In the actual use of vacuum insulation panels, failures due to air leakage often occur. The air leakage points are mostly generated at the heat-sealed edges of the barrier films of vacuum insulation panels. The reason is due to poor sealing areas. Heat-sealing strength is one of the important performance indicators to characterize good sealing. Therefore, the heat-sealing strength of the heat-sealed edges of the barrier films of vacuum insulation panels has always been a quality control factor in the production of vacuum insulation panels.

[0004] The present invention cites the following references:

[0005] In his master's thesis "Synthesis and Characterization of Functionalized POSS Monomers" published in 2010, Zhang Wenhong of Zhejiang University disclosed the chemical structure and preparation method of trihydroxyheptaphenyl POSS. Summary of the invention

[0006] The present invention has developed a new packaging film, which has the technical advantages of high barrier, low thermal conductivity, high sealing strength and wide heat sealing temperature window, and can be used to package thermal runaway-proof injection insulation panels for power lithium batteries.

[0007] A method for preparing a high barrier packaging film comprises the following steps:

[0008] Step 1: preparing a zirconium-containing cage-type silsesquioxane containing a hydrolyzable functional group, and modifying the zirconium-containing cage-type silsesquioxane to the surface of hydroxylated expanded vermiculite by a surface covalent modification method to prepare a composite high-temperature resistant barrier composition;

[0009] Wherein, the zirconium-containing cage-type silsesquioxane containing a hydrolyzable functional group is a monobutoxy zirconium-containing cage-type silsesquioxane monomer or / and a trimethoxy-bridged zirconium-containing cage-type silsesquioxane monomer;

[0010] Step 2: Setting the product structure of the packaging film to include an external protective structure layer, an intermediate barrier structure layer and an internal heat-sealing structure layer, and adopting a co-extrusion blow molding film forming process to prepare a high-barrier packaging film; wherein, 0.5-3wt% of the composite high-temperature resistant barrier composition is added to the external protective structure layer, and 2-5wt% of the composite high-temperature resistant barrier composition is added to the intermediate barrier structure layer.

[0011] Preferably, the preparation method of the monobutoxy zirconium-containing cage-type silsesquioxane monomer is: using trihydroxy heptaphenyl POSS as a raw material, using tetrabutyl zirconate as a capping agent, synthesizing the monobutoxy zirconium-containing cage-type silsesquioxane monomer by a vertex-capping method, and controlling the molar ratio of trihydroxy heptaphenyl POSS and tetrabutyl zirconate to be 1: (1.01~1.05).

[0012] Preferably, the preparation method of the trimethoxy-bridged zirconium-containing cage-type silsesquioxane monomer is:

[0013] The alkenyl functional group of diallylamine reacts with the Si-H bond of dimethylchlorosilane to generate a di(monochlorosilyl) monomer, and the molar ratio of diallylamine to dimethylchlorosilane is controlled to be 1:(2.01-2.05);

[0014] Using a monobutoxy zirconium-containing cage silsesquioxane monomer as a raw material, a zirconium hydroxyl functional group obtained by hydrolyzing the monobutoxy zirconium-containing cage silsesquioxane monomer and a silanol functional group obtained by hydrolyzing a di(monochlorosilyl) monomer undergo a dehydration condensation reaction to generate a bridged zirconium-containing cage silsesquioxane monomer, and the molar ratio of the monobutoxy zirconium-containing cage silsesquioxane monomer to the di(monochlorosilyl) monomer is controlled to be (2.01-2.05):1;

[0015] Utilizing the nucleophilic substitution mechanism, the tertiary amine functional group of the bridged zirconium-containing cage silsesquioxane monomer undergoes a quaternization reaction with the chlorine functional group of 3-chloropropyltrimethoxysilane to generate a trimethoxy-bridged zirconium-containing cage silsesquioxane monomer, and the molar ratio of the bridged zirconium-containing cage silsesquioxane monomer to 3-chloropropyltrimethoxysilane is controlled to be 1:(1.01~1.05).

[0016] Preferably, the structural composition and formula composition of each layer of the high barrier packaging film are as follows:

[0017] The outer protective structure layer consists of the first layer, the second layer and the third layer;

[0018] The formula of the first layer is: 40-80 parts by weight of low-density polyethylene resin LDPE, 15-55 parts by weight of linear low-density polyethylene resin LLDPE, and 1-7 parts by weight of a composite high-temperature resistant barrier composition;

[0019] The formula of the second layer is: 60-80 parts by weight of high-density polyethylene resin HDPE and 20-40 parts by weight of metallocene polyethylene resin m-LLDPE;

[0020] The formula of the third layer is: 60-90 parts by weight of low-density polyethylene resin LDPE and 10-40 parts by weight of metallocene polyethylene resin m-LLDPE;

[0021] The middle barrier structure layer is composed of the fourth layer, the fifth layer and the sixth layer;

[0022] The formula of the fourth layer is: 100 parts by weight of maleic anhydride grafted polyethylene resin PE-g-MAH;

[0023] The formula of the fifth layer is: 50-70 parts by weight of low-density polyethylene resin LDPE, 20-40 parts by weight of ethylene-vinyl alcohol copolymer resin EVOH and 5-10 parts by weight of composite high-temperature resistant barrier composition;

[0024] The formula of the sixth layer is: 100 parts by weight of maleic anhydride grafted polyethylene resin PE-g-MAH;

[0025] The inner heat-sealed structure layer consists of the seventh, eighth and ninth layers:

[0026] The formula of the seventh layer is: 60-90 parts by weight of low-density polyethylene resin LDPE and 10-40 parts by weight of metallocene polyethylene resin m-LLDPE;

[0027] The formula of the eighth layer is: 60-80 parts by weight of high-density polyethylene resin HDPE and 20-40 parts by weight of metallocene polyethylene resin m-LLDPE;

[0028] The formula of the ninth layer is: 20-40 parts by weight of low-density polyethylene resin LDPE, 20-40 parts by weight of linear low-density polyethylene resin LLDPE and 30-50 parts by weight of metallocene polyethylene resin m-LLDPE.

[0029] Preferably, the mass ratio of the first layer, the second layer, the third layer, the fourth layer, the fifth layer, the sixth layer, the seventh layer, the eighth layer and the ninth layer in the high barrier packaging film is (10-20): (5-15): (5-15): (3-8): (10-30): (3-8): (5-15): (5-15): (10-20).

[0030] Preferably, the composite high temperature resistant barrier composition is composed of 5 to 15 parts by weight of hydroxylated expanded vermiculite and 1 to 10 parts by weight of zirconium-containing cage-type silsesquioxane.

[0031] The high barrier packaging film prepared by the above method has a thickness of (130-200) μm and a water vapor transmission rate of (1.0-2.0) g / (m 2 •24h), oxygen permeability is (1.0~1.5)cm 3 / (m 2 •24h•0.1MPa), heat sealing temperature range is (140~190)℃.

[0032] Beneficial effects: The present invention synthesizes a high temperature resistant surface modifier (monobutoxy zirconium-containing cage-type silsesquioxane monomer and trimethoxy bridged zirconium-containing cage-type silsesquioxane monomer), and uses a surface covalent modification method to modify the high temperature resistant surface modifier onto the surface of expanded vermiculite to obtain a composite high temperature resistant barrier composition with excellent dispersion performance;

[0033] A packaging film (a nine-layer co-extruded composite film) was prepared by using a composite high temperature resistant barrier composition as a modifying agent, and the water vapor permeability of the packaging film was reduced to (1.0-2.0) g / (m 2 •24h), oxygen permeability decreased to (1.0~1.5)cm 3 / (m 2 •24h•0.1MPa), the sealing strength is increased to more than 35N / 15mm, the heat sealing temperature range is 140~190℃, and the thermal conductivity is as low as (0.10~0.15)W / (m•K), which has the beneficial technical effects of high barrier performance, high sealing strength and wide sealing temperature range. It can be used to package power lithium battery thermal runaway prevention injection insulation panels. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 is the chemical structural formula of monobutoxy zirconium-containing cage-type silsesquioxane monomer;

[0035] Figure 2 is the chemical structural formula of di(monochlorosilyl) monomer;

[0036] Figure 3 is the chemical structural formula of a bridged zirconium-containing cage-type silsesquioxane monomer;

[0037] Figure 4 is the chemical structural formula of a trimethoxy-bridged zirconium-containing cage-type silsesquioxane monomer;

[0038] Figure 5 It is a bar graph of the performance test results of the packaging film. DETAILED DESCRIPTION Embodiment 1:

[0039] The product structure of packaging film I is: external protective structure layer, middle barrier structure layer and internal heat sealing structure layer;

[0040] Among them, the outer protective structure layer consists of the first layer, the second layer and the third layer;

[0041] The formula of the first layer is: 60 parts by weight of low-density polyethylene resin LDPE (purchased from Jiangsu Rantai Plastic Chemical Co., Ltd., brand LD 150DW), 35 parts by weight of linear low-density polyethylene resin LLDPE (purchased from Yuyao Hongyang Plastic Chemical Co., Ltd., brand 2045G) and 5 parts by weight of composite high-temperature resistant barrier composition;

[0042] The formula of the second layer is: 70 parts by weight of high-density polyethylene resin HDPE (purchased from Dongguan Longhuang Plastic Raw Materials Co., Ltd., brand FB5600) and 30 parts by weight of metallocene polyethylene resin m-LLDPE (purchased from Dongguan Jinshixiang Plastic Raw Materials Co., Ltd., brand SP4020);

[0043] The formula of the third layer is: 80 parts by weight of low-density polyethylene resin LDPE and 20 parts by weight of metallocene polyethylene resin m-LLDPE;

[0044] The composite high temperature resistant barrier composition can be added to any layer of the external protective structure layer; in this embodiment, it is preferably added to the first layer of the external protective structure layer;

[0045] The middle barrier structure layer is composed of the fourth layer, the fifth layer and the sixth layer;

[0046] The formula of the fourth layer is: 100 parts by weight of maleic anhydride grafted polyethylene resin PE-g-MAH (purchased from Dongguan Taotao Plastic Raw Materials Co., Ltd., brand number 4288);

[0047] The formula of the fifth layer is: 60 parts by weight of low-density polyethylene resin LDPE, 30 parts by weight of ethylene-vinyl alcohol copolymer resin EVOH (purchased from Guangzhou Best New Material Technology Co., Ltd., brand ET3803RB) and 8 parts by weight of composite high-temperature resistant barrier composition;

[0048] The formula of the sixth layer is: 100 parts by weight of maleic anhydride grafted polyethylene resin PE-g-MAH;

[0049] The inner heat-sealed structural layer consists of the seventh layer, the eighth layer and the ninth layer;

[0050] The formula of the seventh layer is: 80 parts by weight of low-density polyethylene resin LDPE and 20 parts by weight of metallocene polyethylene resin m-LLDPE;

[0051] The formula of the eighth layer is: 70 parts by weight of high-density polyethylene resin HDPE and 30 parts by weight of metallocene polyethylene resin m-LLDPE;

[0052] The formula of the ninth layer is: 30 parts by weight of low-density polyethylene resin LDPE, 30 parts by weight of linear low-density polyethylene resin LLDPE and 40 parts by weight of metallocene polyethylene resin m-LLDPE;

[0053] The mass ratio of the first layer, the second layer, the third layer, the fourth layer, the fifth layer, the sixth layer, the seventh layer, the eighth layer and the ninth layer in the packaging film I is 15:10:10:5:20:5:10:10:15;

[0054] The formula of the composite high temperature resistant barrier composition is: 7 parts by weight of hydroxylated expanded vermiculite and 3 parts by weight of monobutoxy zirconium-containing cage-type silsesquioxane monomer;

[0055] The chemical structure of the monobutoxy zirconium-containing cage-type silsesquioxane monomer is as follows: Figure 1 As shown, a preparation method of monobutoxy zirconium-containing cage-type silsesquioxane monomer is described in Experimental Example 1; a preparation method of hydroxylated expanded vermiculite is described in Experimental Example 3. Embodiment 2:

[0056] The steps for preparing the encapsulation film I in Example 1 are as follows:

[0057] Step 1, preparing a composite high temperature resistant barrier composition I: using a monobutoxy zirconium-containing cage-type silsesquioxane monomer to undergo a dehydration condensation reaction with the zirconium hydroxyl functional group obtained by the hydrolysis reaction of the monobutoxy zirconium-containing cage-type silsesquioxane monomer and the hydroxyl functional group on the surface of the hydroxylated expanded vermiculite, the monobutoxy zirconium-containing cage-type silsesquioxane monomer is modified on the surface of the expanded vermiculite to obtain a composite high temperature resistant barrier composition I, and the specific preparation steps are: 7g of hydroxylated expanded vermiculite, 80mL of anhydrous ethanol and 20mL of deionized water are added to a beaker, ultrasonically treated for 10min, heated to 40°C, and then 3g of monobutoxy zirconium-containing cage-type silsesquioxane monomer and 2 drops of glacial acetic acid are added to the beaker in turn, stirred for 10h, centrifuged, and repeatedly centrifuged and washed with anhydrous ethanol and deionized water in turn, and then dried in a 50°C vacuum oven and a 110°C oven for 2h in turn to obtain a composite high temperature resistant barrier composition I;

[0058] Step 2: According to the formula of packaging film I, a nine-layer co-extrusion film blowing unit is used to prepare packaging film I with a thickness of 150 μm through a co-extrusion blow molding film forming process.

[0059] Among them, the process parameters of the screw extruder corresponding to the first, second, third, seventh, eighth and ninth layers are set as follows: the temperature of zones 1-3 is 120°C, 150°C and 170°C respectively, the flow channel temperature is 165°C, and the speed is 30r / min;

[0060] The process parameters of the screw extruder corresponding to the fourth and sixth layers were set as follows: the temperatures of zones 1-3 were 125°C, 150°C, and 165°C, respectively, the flow channel temperature was 160°C, and the rotation speed was 15 r / min;

[0061] The process parameters of the screw extruder corresponding to the fifth layer were set as follows: the temperatures of zones 1-3 were 180°C, 200°C, and 210°C, respectively, the flow channel temperature was 205°C, and the rotation speed was 40 r / min;

[0062] Prepare encapsulation film II, the preparation method and steps of which differ from those of encapsulation film I only in that: composite high temperature resistant barrier composition II is used to replace composite high temperature resistant barrier composition I;

[0063] Among them, the preparation method of the composite high temperature resistant barrier composition II is: using the trimethoxy-bridged zirconium-containing cage-type silsesquioxane monomer to undergo a dehydration condensation reaction with the hydroxyl functional groups obtained by the hydrolysis reaction of the trimethoxy-bridged zirconium-containing cage-type silsesquioxane monomer and the hydroxyl functional groups on the surface of the hydroxylated expanded vermiculite, and modifying the trimethoxy-bridged zirconium-containing cage-type silsesquioxane monomer on the surface of the expanded vermiculite to obtain the composite high temperature resistant barrier composition II. The specific preparation steps refer to the preparation experiment of the composite high temperature resistant barrier composition I, and the only difference is that the monobutoxy zirconium-containing cage-type silsesquioxane monomer is replaced by the trimethoxy-bridged zirconium-containing cage-type silsesquioxane monomer;

[0064] The chemical structure of trimethoxy-bridged zirconium-containing cage-type silsesquioxane monomer is as follows: Figure 4 As shown, a preparation method of a trimethoxy-bridged zirconium-containing cage-type silsesquioxane monomer is described in Experimental Example 2.

[0065] Performance Test:

[0066] (1) Determine the water vapor permeability of the product according to GB / T 1037-2021 "Plastic Film and Sheeting - Determination of Water Vapor Permeability - Cup Weight Gain Method";

[0067] (2) Determine the oxygen permeability of the product according to GB / T 1038-2000 "Plastic Film and Sheeting Gas Permeability Test Method - Pressure Difference Method";

[0068] (3) Determine the thermal conductivity of the product according to GB / T 29313-2012 "Test method for thermal conductivity of electrical insulating materials";

[0069] (4) The tensile properties of the product are measured according to GB / T 1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets"; the test speed is 5 mm / min;

[0070] (5) The samples were heat-sealed using an HSG-C heat sealer with a sealing area of ​​15 cm × 1 cm. The heat-sealing temperatures were set at 140 °C, 160 °C, 180 °C, and 190 °C, respectively. The heat-sealing pressure was 0.2 MPa, and the heat-sealing time was 2.0 s.

[0071] According to QB / T 2358-1998 "Test Method for Heat Seal Strength of Plastic Film Packaging Bags", the heat seal performance of the heat seal sample was tested at a test speed of 300mm / min and a clamp spacing of 50mm. The heat seal strength of the sample was recorded.

[0072] The above experimental results are shown in Table 1, Table 2 and Figure 5 .

[0073] Table 1 Performance test results of packaging film

[0074]

[0075] Note: The difference between the comparative example and the encapsulation film Ⅰ is that: the composite high temperature resistant barrier composition Ⅰ is not used;

[0076] Table 2 Performance test results of packaging film II

[0077]

[0078] Note: The difference between the comparative example and the encapsulation film Ⅰ is that: the composite high temperature resistant barrier composition Ⅰ is not used;

[0079] By comprehensively analyzing the above experimental results, the following conclusions can be drawn:

[0080] Conclusion 1: The encapsulation film product prepared by the present invention has achieved significant improvement in barrier properties, heat sealing properties, thermal conductivity and mechanical properties.

[0081] Conclusion 2: The packaging film modified with expanded vermiculite whose surface is modified with zirconium-containing cage silsesquioxane (specifically including monobutoxy zirconium-containing cage silsesquioxane monomer and trimethoxy bridged zirconium-containing cage silsesquioxane monomer) has significantly improved the barrier properties, thermal conductivity and mechanical properties on the one hand, and significantly broadened the heat sealing temperature window on the other hand. The possible mechanism is that the expanded vermiculite modified with zirconium-containing cage silsesquioxane improves the temperature resistance of the outer material of the packaging film, prevents the decomposition of some polymers, and makes the high-temperature deformation of the outer film smaller, which is manifested in the improvement of the heat sealing strength value on a macroscopic level;

[0082] The surface modification of expanded vermiculite using trimethoxy-bridged zirconium-containing cage-type silsesquioxane monomers can significantly improve the heat-sealing properties of the packaging film.

[0083] Experimental Example 1:

[0084] Preparation of monobutoxy zirconium-containing cage-type silsesquioxane monomer: Using trihydroxy heptaphenyl POSS as a raw material and tetrabutyl zirconate as a capping agent, a monobutoxy zirconium-containing cage-type silsesquioxane monomer is synthesized by a vertex-capping method, and the molar ratio of trihydroxy heptaphenyl POSS to tetrabutyl zirconate is controlled to be 1: (1.01-1.05). Its chemical structure is as follows: Figure 1 As shown;

[0085] The specific experimental steps for preparing a monobutoxy zirconium-containing cage-type silsesquioxane monomer are as follows: under the protection of nitrogen, 4.7 g of trihydroxy heptaphenyl POSS and 50 mL of anhydrous tetrahydrofuran are added to a three-necked flask, stirred at room temperature until completely dissolved, and then placed in an ice-water bath, 1.9 mL of tetrabutyl zirconate is added dropwise to the three-necked flask, stirred in the ice-water bath for reaction for 30 min, and then the ice-water bath is removed, and the stirring reaction is continued at room temperature for 6 h, the solvent is removed by rotary evaporation, and concentrated to a saturated solution, acetonitrile is used for sedimentation, filtration, washing, and vacuum drying to obtain a monobutoxy zirconium-containing cage-type silsesquioxane monomer;

[0086] The nuclear magnetic resonance hydrogen spectrum of the monobutoxy zirconium-containing cage-type silsesquioxane monomer is characterized as follows: 1 H NMR (CDCl3, 400MHz) δ: 0.92-0.96 (t, 3H), 1.40-1.49 (m, 2H), 1.86-1.93 (m, 2H), 3.68-3.71 (t, 2H), 7.32-7.56 (m, 35H, Ar-H).

[0087] Experimental Example 2:

[0088] The trimethoxy-bridged zirconium-containing cage-type silsesquioxane monomer is prepared, and the preparation steps are as follows:

[0089] Step 1: The alkenyl functional group of diallylamine reacts with the Si-H bond of dimethylchlorosilane to generate a di(monochlorosilyl) monomer, and the molar ratio of diallylamine to dimethylchlorosilane is controlled to be 1:(2.01~2.05). Its chemical structure is as follows: Figure 2 As shown;

[0090] The second step: using a monobutoxy zirconium-containing cage silsesquioxane monomer as a raw material, a zirconium hydroxyl functional group obtained by hydrolysis of the monobutoxy zirconium-containing cage silsesquioxane monomer and a silanol functional group obtained by hydrolysis of a di(monochlorosilyl) monomer undergo a dehydration condensation reaction to generate a bridged zirconium-containing cage silsesquioxane monomer, and controlling the molar ratio of the monobutoxy zirconium-containing cage silsesquioxane monomer to the di(monochlorosilyl) monomer to be (2.01-2.05):1, and its chemical structure is as follows: Figure 3 As shown;

[0091] Step 3: Using the nucleophilic substitution mechanism, the tertiary amine functional group of the bridged zirconium-containing cage silsesquioxane monomer reacts with the chlorine functional group of 3-chloropropyltrimethoxysilane to generate a trimethoxy bridged zirconium-containing cage silsesquioxane monomer, and the molar ratio of the bridged zirconium-containing cage silsesquioxane monomer to 3-chloropropyltrimethoxysilane is controlled to be 1: (1.01-1.05). Its chemical structure is as follows: Figure 4 As shown;

[0092] The specific experimental steps for preparing trimethoxy-bridged zirconium-containing cage-type silsesquioxane monomers are as follows:

[0093] Under nitrogen protection, 1.1 g and 30 mL of anhydrous tetrahydrofuran were added to a three-necked flask, stirred at room temperature until completely dissolved, and then 2.2 mL of dimethylchlorosilane was added dropwise to the three-necked flask. After stirring at room temperature for 15 min, 4 drops of Custer catalyst were added dropwise, the temperature was raised to 60 ° C, stirred and reacted for 4 h, cooled to room temperature, the solvent was removed by rotary evaporation, and vacuum dried to obtain a di(monochlorosilyl) monomer;

[0094] Under the protection of nitrogen, 10.9g of monobutoxy zirconium-containing cage-type silsesquioxane monomer and 100mL of anhydrous tetrahydrofuran were added to a three-necked flask, stirred at room temperature until completely dissolved, and then placed in an ice-water bath, 10mL of anhydrous tetrahydrofuran solution containing 1.5g of di(monochlorosilyl) monomer was added dropwise to the three-necked flask, stirred in the ice-water bath for 30min, and then the ice-water bath was removed, and the stirring reaction was continued at room temperature for 8h, the solvent was removed by rotary evaporation, and concentrated to a saturated solution, acetonitrile was used for precipitation, filtration, washing, and vacuum drying to obtain a bridged zirconium-containing cage-type silsesquioxane monomer;

[0095] 5.8 g of bridged zirconium-containing cage silsesquioxane monomer and 50 mL of anhydrous tetrahydrofuran were added to a three-necked flask, stirred at room temperature until completely dissolved, and then 0.5 mL of 3-chloropropyltrimethoxysilane was added dropwise to the three-necked flask, heated to 50° C. and stirred for 10 h, cooled to room temperature and then rotary evaporated to remove the solvent, washed with ethyl acetate, and vacuum dried to obtain a trimethoxy-bridged zirconium-containing cage silsesquioxane monomer;

[0096] The nuclear magnetic resonance hydrogen spectrum of the trimethoxy-bridged zirconium-containing cage-type silsesquioxane monomer is characterized as follows: 1 H NMR (CDCl3, 400MHz) δ: 0.23 (s, 12H), 0.91-0.94 (t, 2H), 1.15-1.19 (t, 4H), 1.63-1.70 (m, 4H), 1.84-1.91 (m, 2H) , 3.05 (s, 3H), 3.37-3.40 (t, 4H), 3.58 (s, 9H), 3.76-3.79 (t, 2H), 7.32-7.56 (m, 70H, Ar-H).

[0097] Experimental Example 3:

[0098] Preparation of hydroxylated expanded vermiculite: expanded vermiculite powder (purchased from the mineral processing plant in Lingshou County, Hebei Province, with an impurity content of <0.8%) was placed in a planetary ball mill for grinding. The ball mill speed was set to 600 r / min and the ball milling time was set to 15 min to obtain expanded vermiculite powder after ball milling. Then, 10 g of the expanded vermiculite powder after ball milling and 200 mL of a hydrogen peroxide solution (30 wt %) were added to a round-bottom flask, and the mixture was evenly dispersed by ultrasonic treatment for 10 min. Under mechanical stirring, the mixture was heated to 105 ° C and refluxed for 6 h. After cooling, the mixture was centrifuged at 5000 rpm for 5 min, washed 3 times with deionized water, and dried under vacuum at 80 ° C for 5 h to obtain hydroxylated expanded vermiculite.

Claims

1. A method for preparing a high barrier packaging film, characterized in that: The steps include: Step 1: preparing a zirconium-containing cage-type silsesquioxane containing a hydrolyzable functional group, and modifying the zirconium-containing cage-type silsesquioxane to the surface of hydroxylated expanded vermiculite by a surface covalent modification method to prepare a composite high-temperature resistant barrier composition; Wherein, the zirconium-containing cage-type silsesquioxane containing a hydrolyzable functional group is a monobutoxy zirconium-containing cage-type silsesquioxane monomer or / and a trimethoxy-bridged zirconium-containing cage-type silsesquioxane monomer; The chemical structural formula of the monobutoxy zirconium-containing cage-type silsesquioxane monomer is: ; The chemical structural formula of the trimethoxy-bridged zirconium-containing cage-type silsesquioxane monomer is: ; Step 2: Setting the product structure of the packaging film to include an external protective structure layer, an intermediate barrier structure layer and an internal heat-sealing structure layer, and adopting a co-extrusion blow molding film forming process to prepare a high-barrier packaging film; wherein, 0.5-3wt% of the composite high-temperature resistant barrier composition is added to the external protective structure layer, and 2-5wt% of the composite high-temperature resistant barrier composition is added to the intermediate barrier structure layer.

2. The method for preparing a high barrier packaging film according to claim 1, characterized in that: The preparation method of the monobutoxy zirconium-containing cage-type silsesquioxane monomer comprises the following steps: using trihydroxy heptaphenyl POSS as a raw material, using tetrabutyl zirconate as a capping agent, synthesizing the monobutoxy zirconium-containing cage-type silsesquioxane monomer by a vertex-capping method, and controlling the molar ratio of trihydroxy heptaphenyl POSS to tetrabutyl zirconate to be 1:(1.01-1.05).

3. The method for preparing a high barrier packaging film according to claim 1, characterized in that: The preparation method of the trimethoxy-bridged zirconium-containing cage-type silsesquioxane monomer is as follows: The alkenyl functional group of diallylamine reacts with the Si-H bond of dimethylchlorosilane to generate a di(monochlorosilyl) monomer, and the molar ratio of diallylamine to dimethylchlorosilane is controlled to be 1:(2.01-2.05); Using a monobutoxy zirconium-containing cage silsesquioxane monomer as a raw material, a zirconium hydroxyl functional group obtained by hydrolyzing the monobutoxy zirconium-containing cage silsesquioxane monomer and a silanol functional group obtained by hydrolyzing a di(monochlorosilyl) monomer undergo a dehydration condensation reaction to generate a bridged zirconium-containing cage silsesquioxane monomer, and the molar ratio of the monobutoxy zirconium-containing cage silsesquioxane monomer to the di(monochlorosilyl) monomer is controlled to be (2.01-2.05):1; Utilizing the nucleophilic substitution mechanism, the tertiary amine functional group of the bridged zirconium-containing cage silsesquioxane monomer undergoes a quaternization reaction with the chlorine functional group of 3-chloropropyltrimethoxysilane to generate a trimethoxy-bridged zirconium-containing cage silsesquioxane monomer, and the molar ratio of the bridged zirconium-containing cage silsesquioxane monomer to 3-chloropropyltrimethoxysilane is controlled to be 1:(1.01~1.05).

4. The method for preparing a high barrier packaging film according to claim 1, characterized in that: The structural composition and formula composition of each layer of the high barrier encapsulation film are as follows: The outer protective structure layer consists of the first layer, the second layer and the third layer; The formula of the first layer is: 40-80 parts by weight of low-density polyethylene resin LDPE, 15-55 parts by weight of linear low-density polyethylene resin LLDPE, and 1-7 parts by weight of a composite high-temperature resistant barrier composition; The formula of the second layer is: 60-80 parts by weight of high-density polyethylene resin HDPE and 20-40 parts by weight of metallocene polyethylene resin m-LLDPE; The formula of the third layer is: 60-90 parts by weight of low-density polyethylene resin LDPE and 10-40 parts by weight of metallocene polyethylene resin m-LLDPE; The middle barrier structure layer is composed of the fourth layer, the fifth layer and the sixth layer; The formula of the fourth layer is: 100 parts by weight of maleic anhydride grafted polyethylene resin PE-g-MAH; The formula of the fifth layer is: 50-70 parts by weight of low-density polyethylene resin LDPE, 20-40 parts by weight of ethylene-vinyl alcohol copolymer resin EVOH and 5-10 parts by weight of composite high-temperature resistant barrier composition; The formula of the sixth layer is: 100 parts by weight of maleic anhydride grafted polyethylene resin PE-g-MAH; The inner heat-sealed structure layer consists of the seventh, eighth and ninth layers: The formula of the seventh layer is: 60-90 parts by weight of low-density polyethylene resin LDPE and 10-40 parts by weight of metallocene polyethylene resin m-LLDPE; The formula of the eighth layer is: 60-80 parts by weight of high-density polyethylene resin HDPE and 20-40 parts by weight of metallocene polyethylene resin m-LLDPE; The formula of the ninth layer is: 20-40 parts by weight of low-density polyethylene resin LDPE, 20-40 parts by weight of linear low-density polyethylene resin LLDPE and 30-50 parts by weight of metallocene polyethylene resin m-LLDPE.

5. The method for preparing a high barrier packaging film according to claim 4, characterized in that: The mass ratio of the first layer, the second layer, the third layer, the fourth layer, the fifth layer, the sixth layer, the seventh layer, the eighth layer and the ninth layer in the high barrier packaging film is (10-20): (5-15): (5-15): (3-8): (10-30): (3-8): (5-15): (5-15): (10-20).

6. The method for preparing a high barrier packaging film according to claim 1, characterized in that: The composite high temperature resistant barrier composition consists of 5 to 15 parts by weight of hydroxylated expanded vermiculite and 1 to 10 parts by weight of zirconium-containing cage-type silsesquioxane.

7. A high barrier packaging film prepared by the method according to any one of claims 1 to 6, characterized in that: The thickness of the high barrier packaging film is (130-200) μm, and the water vapor permeability is (1.0-2.0) g / (m 2 •24h), oxygen permeability is (1.0~1.5)cm 3 / (m 2 •24h•0.1MPa), heat sealing temperature range is (140~190)℃.

8. A high barrier packaging film prepared by the method according to any one of claims 1 to 6, characterized in that: The high-barrier packaging film is used for packaging a thermal runaway-proof spray insulation board for a power lithium battery.